Free-Radical Scavenging and Antioxidant Properties of Melatonin (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Melatonin is an indoleamine that has captured our attention since 1958. It was discovered as one of the main regulators of circadian rhythms. At that time, it was simply defined as the sleep–wake regulator hormone, as melatonin is mainly secreted by the pineal gland during the night. Its role in seasonal reproductive functions was also found very soon after. Later, the extra-pineal synthesis of melatonin was discovered (immune system, retina, etc.), together with its production in other organisms, such as bacteria and plants. This fact changed the idea that melatonin was just a hormone that synchronized processes related with the circadian and seasonal rhythms and brought up the role of melatonin as a very potent antioxidant. With this Special Issue, we aim to explore the most recent roles of melatonin as an antioxidant, and we provide a great deal of new information: from melatonin synthesis in a new domain to recent uses of melatonin as a therapy and synergistic treatment for cancer. Thus, we are sure that this indoleamine will be in the spotlight for much more time to come.